Aktualisasi buku “Merancang Website Pendidikan Bagi Pemula” - Kunto Imbar Nursetyo (Jurnal Pembelajaran Inovatif, 2022)
Educational institutions must always innovate in utilizing technology as a medium in improving the quality and service of education. The Education Website can be a means of communication between institutions and students, stakeholders and many other parties in providing important information. If an educational institution does not have a website, then the educational institution will lose benefits. This is an opportunity for graduates of the S1 Educational Technology Study Program to reach this large area. During the Pandemic and almost all require the profile of graduates of the S1 Educational Technology Study Program, one of the things that is sought after from this graduate is the ability to develop an Education website. On this basis, a teaching material is needed that can be used for students of the Educational Technology Study Program to learn the basics of producing an Education website. One of the efforts made is to develop a Book Designing an Educational Website for Beginners with a specific target for all Educational Technology students throughout Indonesia and for the general public. However, to ensure that quality has been achieved, it is necessary to look at the actualization of the Book designing an Educational Website for Beginners. Therefore, from this research, it is hoped that it can obtain data on the actualization of the Book designing an Educational Website for Beginners in the Educational Technology Study Program. This research will actualize the book Designing an Educational Website for Beginners in the S1 Educational Technology Study Program at Lambung Mangkurat University. In particular, this study will carry out the dissemination as follows: 1) Implementation. At the implementation stage there are 3 main functions, namely conveying, managerial and supporting functions. 2) Evaluation. The evaluation stage that will be carried out is a summative evaluation. From these stages, this research has ipr outputs and ISBN books. Abstrak Lembaga pendidikan harus selalu melakukan inovasi dalam memanfaatkan teknologi sebagai media dalam meningkatkan mutu dan layanan pendidikan. Website Pendidikan bisa menjadi sebuah sarana komunikasi antara lembaga dan peserta didik, stakeholder dan banyak pihak lainnya dalam memberikan informasi penting. Jika sebuah lembaga Pendidikan tidak memiliki website, maka lembaga Pendidikan pun akan kehilangan manfaat. Hal ini menjadi sebuah peluang bagi lulusan Program Studi S1 Teknologi Pendidikan untuk menjamah wilayah garapan yang besar ini. Disaat Pandemi dan hampir seluruh membutuhkan profil lulusan Program Studi S1 Teknologi Pendidikan, salah satu yang dicari dari lulusan ini adalah kemampuan mengembangkan website Pendidikan. Atas dasar hal tersebut, maka dibutuhkan sebuah bahan ajar yang dapat digunakan untuk para mahasiswa Program Studi Teknologi Pendidikan mempelajari dasar-dasar dari membuah sebuah website Pendidikan. Salah satu upaya yang dilakukan adalah dengan mengembangan Buku Merancang Website Pendidikan Bagi Pemula dengan sasaran khusus seluruh mahasiswa Teknologi Pendidikan seluruh Indonesia dan bagi khalayak umum. Namun untuk memastikan kualitas telah tercapai, maka perlu dilihat aktualisasi dari Buku Merancang Website Pendidikan Bagi Pemula. Oleh karena itu dari penelitian ini diharapkan dapat memperoleh data aktualisasi Buku Merancang Website Pendidikan Bagi Pemula di Program Studi Teknologi Pendidikan. Penelitian ini akan melakukan Aktualisasi buku Merancang Website Pendidikan Bagi Pemula di Program Studi S1 Teknologi Pendidikan Universitas Lambung Mangkurat. Secara khusus penelitian ini akan melakukan desiminasi sebagai berikut: 1) Implementasi. Pada tahap implementasi terdapat 3 fungsi utama, yaitu fungsi menyampaikan, manajerial dan fungsi pendukung. 2) Evaluasi. Tahap evaluasi yang akan dilaksanakan adalah evaluasi sumatif. Dari tahapan tersebut, penelitian ini memiliki Luaran HKI dan Buku Ber-ISBN.